Infection Process and Genome Assembly Provide Insights into the Pathogenic Mechanism of Destructive Mycoparasite Calcarisporium cordycipiticola with Host Specificity - Qing Liu (MDPI AG, 2021)
Calcarisporium cordycipiticola is the pathogen in the white mildew disease of Cordyceps militaris, one of the popular mushrooms. This disease frequently occurs and there is no effective method for disease prevention and control. In the present study, C. militaris is found to be the only host of C. cordycipiticola, indicating strict host specificity. The infection process was monitored by fluorescent labeling and scanning and transmission electron microscopes. C. cordycipiticola can invade into the gaps among hyphae of the fruiting bodies of the host and fill them gradually. It can degrade the hyphae of the host by both direct contact and noncontact. The parasitism is initially biotrophic, and then necrotrophic as mycoparasitic interaction progresses. The approximate chromosome-level genome assembly of C. cordycipiticola yielded an N50 length of 5.45 Mbp and a total size of 34.51 Mbp, encoding 10,443 proteins. Phylogenomic analysis revealed that C. cordycipiticola is phylogenetically close to its specific host, C. militaris. A comparative genomic analysis showed that the number of CAZymes of C. cordycipiticola was much less than in other mycoparasites, which might be attributed to its host specificity. Secondary metabolite cluster analysis disclosed the great biosynthetic capabilities and potential mycotoxin production capability. This study provides insights into the potential pathogenesis and interaction between mycoparasite and its host.